HLA‐DQ2/DQ8 and HLA‐DQB1*02 homozygosity typing by real‐time polymerase chain reaction for the assessment of celiac disease genetic risk: evaluation of a Spanish celiac population. Issue 6 (December 2014) - Ruiz‐Ortiz, E.; Montraveta, M.; Cabré, E.; Herrero‐Mata, M. J.; Pujol‐Borrell, R.; Palou, E.; Faner, R.
Abstract Celiac disease (CD) is a complex autoimmune disorder caused by ingestion of gluten in genetically susceptible individuals. Different genetic risk factors have been identified, but virtually all patients are human leukocyte antigen (HLA)‐DQ2 and/or HLA‐DQ8 positive. We describe a new, fast, accurate and simple real‐time polymerase chain reaction (PCR)‐based assay for the genotyping and homozygosity analysis of the CD‐related HLA alleles. The assay overcomes the major limitations of protocols currently in use, allowing HLA‐DQ2/DQ8 genotyping by using only three real‐time PCR reactions. For the appraisal of DQ2 homozygosity, only one more reaction is needed. These reactions are easily automated and suitable for large screening studies in diagnostic procedures, as it is demonstrated by their successful application in our HLA diagnostic laboratory. Finally, we assessed the clinical relevance of this real‐time PCR‐based assay by studying a cohort of fully characterized patients. As expected, all CD patients had at least one of the CD‐associated alleles, and the highest CD risk was indicated by the presence of the HLA‐DQ2.5 heterodimer (HLA‐DQA1*05‐DQB1*02) with HLA‐DQB1*02 in homozygosity.